A magical match - Blackwell, Juliet (Blackwell, Juliet. Witchcraft mystery series., 2018)
Lily Ivory and her friends are planning a 1950s-themed brunch to benefit the local women's shelter. When a figure from her past shows up unannounced, threatening her unless she returns something that belonged to him, Lily's fiancé, Sailor, steps in to defend her. After the same man is found dead later that day, Sailor is the primary suspect. He swears he's innocent, but multiple witnesses ID him as the perpetrator of the assault. Lily vows to clear his name...only she's not sure where to start with the mounting evidence against him. When she sees Sailor in the neighborhood despite knowing he's in jail, Lily starts to wonder if there could be a doppelganger in San Francisco. When she's not busy helping customers find matching outfits for the upcoming event, searching for a vintage wedding dress for her own nuptials, and dealing with an ill-timed magical cold, Lily begins to suspect one of her magical foes is targeting her loved ones in an attempt to weaken her.